Assessment of Growth and Psychosocial Problems of Children with Bronchial Asthma - Remya, V.; Deepa, P. (Indian Journal of Nursing Sciences, 2024)
Aim: The aim of the study was to assess the growth and psychosocial problems of children with bronchial asthma. Background: India establishes 3–5% of the global burden on childhood asthma. Psychosocial problems such as emotional, behavioral, and educational problems are highly prevalent among children and can severely interfere with everyday functioning. Methods: A descriptive cross-sectional study design was used. It was conducted among 140 children with bronchial asthma between the age group of 4–12 years and their caregivers who satisfied the sampling criteria. The tools used were socio-personal and clinical data sheet, an anthropometric measurement sheet, and Pediatric Symptom Checklist. Results: In growth monitoring, 11.4% of children had stunting, 6% of children were above the 97th percentile of height, 7.1% of children were underweight and 1.5% of children were above the 97th percentile of weight. It was found that 4.3% of children were having difficulty in psychosocial functioning. It was also seen that 12.9%, 4.3%, and 5% of children were having difficulty functioning in the domains of internalizing, attention, and externalizing, respectively. Conclusion: Early detection and management of growth problems and psychosocial dysfunction are essential to prevent growth faltering and abnormal psychosocial development of children with bronchial asthma